2009
DOI: 10.1002/ar.21002
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Serial Section Computer Reconstruction of the Arrangement of the Structural Components of the Parabronchus of the Ostrich, Struthio Camelus Lung

Abstract: The Ostrich, Struthio camelus is the largest extant bird. The arrangement of the airway and the vascular components of the parabronchus of its lung were investigated by 3D serial section reconstruction. Modestly developed atrial muscles, shallow atria, paucity of infundibulae with preponderant origination of the air capillaries (ACs) from the atria and lack of interparabronchial septa, structural features that epitomize lungs of most highly derived metabolically active volant birds were observed. Intertwined v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 56 publications
0
23
1
Order By: Relevance
“…Using latex casting and scanning electron microscopy (Maina 1982b(Maina , 1988 and three-dimensional (3-D) computer reconstruction from serial sections Maina 2005, 2008;Maina and Woodward 2009), it has been shown that the air capillaries are round structures that interconnect across short, narrow passageways while the blood capillaries are short interconnected segments that are about as long as they are wide . The investigations by Maina (2005, 2008) and Maina and Woodward (2009) (Fig.…”
Section: Bronchial (Airway) Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Using latex casting and scanning electron microscopy (Maina 1982b(Maina , 1988 and three-dimensional (3-D) computer reconstruction from serial sections Maina 2005, 2008;Maina and Woodward 2009), it has been shown that the air capillaries are round structures that interconnect across short, narrow passageways while the blood capillaries are short interconnected segments that are about as long as they are wide . The investigations by Maina (2005, 2008) and Maina and Woodward (2009) (Fig.…”
Section: Bronchial (Airway) Systemmentioning
confidence: 99%
“…The investigations by Maina (2005, 2008) and Maina and Woodward (2009) (Fig. 52) and a freeze fracture preparation (Fig.…”
Section: Bronchial (Airway) Systemmentioning
confidence: 99%
“…Morphologically, the ACs and the BCs differ from the general definition of a eapillary. Regarding their layout, the observation made on the BCs of the lung of the Museovy duek by Maina (2005, 2008) and the ostrieh {Struthio camelus-, Maina and Woodward 2009) differ from that made by Duneker (1974, p. 17) that the BCs "run without intereonneetions straight through the parabronchial wall towards the lumen, bending only slightly on this course." From their sizes, shapes, and spatial arrangement, notwithstanding the compactness of the exchange tissue, the ACs and the BCs are not mirror images, as was claimed by West et al (1977).…”
Section: Form and Arrangement Of The Acs And Bcs Of The Avian Lungmentioning
confidence: 61%
“…The word "eapillary" derives from Latin and means "hairlike," that is, a eord or tubelike strueture that is longer than it is wide. There is now overwhelming evidenee that the ACs and the BCs anastomose profusely as they intimately intertwine with eaeh other (e.g., Duneker 1974, p. 2;West et al 1977, p. 557;Maina 1988, p. 146;Maina 2005, 2008;Maina and Woodward 2009). Moreover, it has reeently been shown by serial-seetion three-dimensional eomputer reeonstruetion Maina 2005, 2008) on the lung of the Museovy duek {Cairina moschata) that the ACs are formed of spherieal (globular) units that are intereonneeted by short, narrow passageways (Woodward and Maina 2005; Fig.…”
Section: Form and Arrangement Of The Acs And Bcs Of The Avian Lungmentioning
confidence: 96%
“…1 and 2, the alveolar septum mostly consists of wideopen blood capillaries with variously shaped erythrocytes, suggesting that networks of the alveolar capillaries were dynamically changing under the expiration and inspiration cycle conditions. Three-dimensional imaging of blood vessel structures in living mouse lung tissues were used to analyze physiological and pathological conditions for the gas exchange in blood-air barriers (Maina and Woodward 2009;Woodward and Maina 2008). Beigelmar-Aubry et al (2005) already reported that lobular structures of lung tissues consisted of basic blood vessel networks, in which centrilobular pulmonary arteries were surrounded by pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%